Analysis Of The Implementation Of The Responsibility Accounting System In The Ilir Talo Sub-District Seluma District - Aldino Erinsyah Putra; Neri Susanti; Kamelia Astuty (Penerbit Jurnal Indonesia, 2023)
The purpose of this research is to determine the implementation of the accountability accounting system at the Ilir Talo sub-district office, Seluma Regency. This research was conducted using a descriptive approach. The research location is one of the sub-district offices in Seluma Regency. Data collection techniques were carried out using observation, interviews, documentation. The results of the research show that the Ilir Talo Subdistrict Office has not implemented responsibility accounting that is in accordance with Mulyadi's responsibility accounting due to a lack of understanding of responsibility accounting, there are only a few items that are appropriate.